Development of learning media to improve writing skills with the theme of love for the homeland - Azza Kharisma, Fadhikka; Sukartiningsih, Wahyu (Journal of diversity in learning (JDIL), 2025)
Picture Series is a collection of images arranged sequentially according to the storyline. This study aims to develop a learning media for the Love Indonesia material to improve writing skills for Grade 5 elementary school students. This research applies the ADDIE development model, consisting of several stages: Analysis, Design, Development, Implementation, and Evaluation. This study produced a learning media assessed by two validators: a material expert, who gave a score of 92%, and a media expert, who gave a score of 94%, both of which fall under the "very feasible" category. The students’ responses were obtained through three stages of trials: the individual trial, which scored 95%; the small group trial, which scored 94%; and the large group trial, which scored 86% — all categorized as "very valid." These results indicate that the development of this picture series-based learning media is feasible to be implemented in classroom learning activities.